Dynamin 1 is important for microtubule organization and stabilization in glomerular podocytes. Issue 12 (17th October 2020) - La, The Mon; Tachibana, Hiromi; Li, Shun‐Ai; Abe, Tadashi; Seiriki, Sayaka; Nagaoka, Hikaru; Takashima, Eizo; Takeda, Tetsuya; Ogawa, Daisuke; Makino, Shin‐ichi; Asanuma, Katsuhiko; Watanabe, Masami; et al.
Abstract: Dynamin 1 is a neuronal endocytic protein that participates in vesicle formation by scission of invaginated membranes. Dynamin 1 is also expressed in the kidney; however, its physiological significance to this organ remains unknown. Here, we show that dynamin 1 is crucial for microtubule organization and stabilization in glomerular podocytes. By immunofluorescence and immunoelectron microscopy, dynamin 1 was concentrated at microtubules at primary processes in rat podocytes. By immunofluorescence of differentiated mouse podocytes (MPCs), dynamin 1 was often colocalized with microtubule bundles, which radially arranged toward periphery of expanded podocyte. In dynamin 1‐depleted MPCs by RNAi, α‐tubulin showed a dispersed linear filament‐like localization, and microtubule bundles were rarely observed. Furthermore, dynamin 1 depletion resulted in the formation of discontinuous, short acetylated α‐tubulin fragments, and the decrease of microtubule‐rich protrusions. Dynamins 1 and 2 double‐knockout podocytes showed dispersed acetylated α‐tubulin and rare protrusions. In vitro, dynamin 1 polymerized around microtubules and cross‐linked them into bundles, and increased their resistance to the disassembly‐inducing reagents Ca 2+ and podophyllotoxin. In addition, overexpression and depletion of dynamin 1 in MPCs increased and decreased the nocodazole resistance of microtubules, respectively. These results suggest that dynamin 1 supports the microtubule bundle formation and participates in the stabilization of microtubules.